Portable Apparatus for In Situ X-Ray Diffraction and Fluorescence Analyses of Artworks - Eveno, Myriam; Moignard, Brice; Castaing, Jacques (Microscopy and microanalysis, 2011)
A portable X-ray fluorescence/X-ray diffraction (XRF/XRD) system for artwork studies has been designed constructed and tested. It is based on Debye Scherrer XRD in reflection that takes advantage of many recent improvements in the handling of X-rays (polycapillary optics; advanced two-dimensional detection). The apparatus is based on a copper anode air cooled X-ray source, and the XRD analysis is performed on a 5–20 μm thick layer from the object surface. Energy dispersive XRF elemental analysis can be performed at the same point as XRD, giving elemental compositions that support the interpretation of XRD diagrams. XRF and XRD analyses were tested to explore the quality and the limits of the analytical technique. The XRD diagrams are comparable in quality with diagrams obtained with conventional laboratory equipment. The mineral identification of materials in artwork is routinely performed with the portable XRF-XRD system. Examples are given for ceramic glazes containing crystals and for paintings where the determination of pigments is still a challenge for nondestructive analysis. For instance, lead compounds that provide a variety of color pigments can be easily identified as well as a pigment such as lapis lazuli that is difficult to identify by XRF alone. More than 70 works of art have been studied in situ in museums, monuments, etc. In addition to ceramics and paintings, these works include bronzes, manuscripts, etc., which permit improvement in the comprehension of ancient artistic techniques.